2010
DOI: 10.1007/s10086-010-1116-3
|View full text |Cite
|
Sign up to set email alerts
|

Strength properties of laminated veneer lumber in compression perpendicular to its grain

Abstract: Tests of compression perpendicular to the grain were carried out on laminated veneer lumber (LVL) and timber. The species tested were sugi, radiata pine, karamatsu, akamatsu, and dahurian larch; two sets of sugi specimens were tested, with the sugi LVL products being manufactured in different plants. The strength properties of the materials for different loading directions were compared for LVL and timber. At 5% compressive strain in the same materials, the average stress in the tangential direction of timber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 1 publication
2
9
0
Order By: Relevance
“…The results obtained in this study were also seen in Norway spruce (Picea abies) [22] and hinoki (C. obtusa) [23]. In contrast, σ e5% under loading in the tangential direction was larger than that under loading in the radial direction in four coniferous tree species [5]. As the reason for the larger σ e5% under loading in the tangential direction, it was considered that vertically lined latewood protected the weak earlywood from being crushed [5].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The results obtained in this study were also seen in Norway spruce (Picea abies) [22] and hinoki (C. obtusa) [23]. In contrast, σ e5% under loading in the tangential direction was larger than that under loading in the radial direction in four coniferous tree species [5]. As the reason for the larger σ e5% under loading in the tangential direction, it was considered that vertically lined latewood protected the weak earlywood from being crushed [5].…”
Section: Discussionsupporting
confidence: 71%
“…In contrast, σ e5% under loading in the tangential direction was larger than that under loading in the radial direction in four coniferous tree species [5]. As the reason for the larger σ e5% under loading in the tangential direction, it was considered that vertically lined latewood protected the weak earlywood from being crushed [5]. In the Japanese larch (Larix kaempferi), the σ e with loading in the tangential direction increased with density; however, the σ e with loading in the radial direction did not correlate with density [24].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…There is much less latewood than earlywood in corewood, but with its smaller cell lumen and thicker cell walls, latewood resists buckling and crushing failure more than early wood [67]. The tighter radius growth rings in the pith samples contribute to the higher strength in clear and resin samples because the latewood acts as a pillar and protects the weaker earlywood from crushing [68] and from dependence on rolling shear properties which are weaker than CPerpG properties [36]. Kijidani, et al [69] also found higher CPerpG strength values for pith samples in Sugi wood and although they could not conclude the reason, they did find correlations with high microfibril angle, increased density in the pith samples as well as cellular structure.…”
Section: Effect Of Pithmentioning
confidence: 99%
“…Poplar laminated veneer lumber (LVL) sheets are fabricated by hotpressing poplar veneer. Because of its excellent physical and mechanical properties, LVL has been applied widely to wooden-structured buildings and is suitable for the development of green and prefabricated buildings [5][6][7][8]. Microscopic and macroscopic defects or damage (cracks) naturally occur in wood [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%